UNIT 14.39 Analysis and Purification of Mouse Intestinal Dendritic Cell and Macrophage Subsets by Flow Cytometry. (1st August 2016) - Koscsó, Balázs; Bogunovic, Milena
Abstract : The unit presents a method for analysis of intestinal dendritic cell (DC) and macrophage subsets by flow cytometry in the single cell suspension prepared from the mouse small and large intestine (Basic Protocol ). ALTERNATE PROTOCOL 1 describes a strategy to enrich the hematopoietic cell fraction in the sample by Percoll gradient centrifugation, and ALTERNATE PROTOCOL 2 describes preparation of single cell suspensions from specific tissue layers of the small intestine, such as the epithelium, villi mucosa, submucosa, and muscularis externa. Finally, Support Protocol explains how to purify specific intestinal DC and macrophage subsets by flow‐cytometry‐based cell sorting. © 2016 by John Wiley & Sons, Inc.